Neurovestibular Dysfunction and Falls in Parkinson's Disease and Atypical Parkinsonism: A Prospective 1 Year Follow-Up Study - Venhovens, Jeroen; Meulstee, Jan; Bloem, Bas R.; Verhagen, Wim I. M. (Frontiers in Neurology, 2020)
Our primary aim was to determine whether neurovestibular laboratory tests can predict future falls in patients with either Parkinson’s disease (PD) or atypical parkinsonism (AP). We included 25 healthy subjects, 30 PD patients (median Hoehn and Yahr stage 2.5, range 1-4), and 14 AP patients (6 multiple system atrophy, 3 progressive supranuclear palsy, and 5 vascular parkinsonism) in a case-control study design (all matched for age and gender). At baseline, all subjects underwent clinical neurological and neurotological assessments, cervical and ocular vestibular evoked myogenic potentials (VEMP), brainstem auditory evoked potentials (BAEP), subjective visual vertical measurements (SVV), and video nystagmography with caloric and rotary test stimulation. After one year follow-up, all subjects were contacted by telephone for an interview about their fall frequency (based upon fall diaries) and about their balance confidence (according to the ABC-16 questionnaire); only one participant was lost to follow-up (attrition bias of 1.4%). Cervical and ocular VEMPs combined with clinical tests for postural imbalance predicted future fall incidents in both PD and AP groups with a sensitivity of 100%. A positive predictive value of 68% was achieved, if only one VEMP test was abnormal, and of 83% when both VEMP tests were abnormal. The fall frequency at baseline and after one year was significantly higher and the balance confidence scale (ABC-16) was significantly lower in both the PD and AP groups compared to healthy controls. Therefore, VEMP testing can predict the risk of future fall incidents in PD and AP patients with postural imbalance.